Preparation method of modified nano composite diaphragm for alkaline electrolyzed water
Through the combination of amino acid modification and polymer, a modified nanocomposite membrane with strong alkali corrosion resistance and good hydrophilicity was prepared, which solved the problems of high surface resistance, poor hydrophilicity and low porosity of the existing porous inorganic composite membrane. Its performance in alkaline electrolyzed water is significantly improved.
Patent Information
- Application Number
- CN202411456480.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
The existing porous inorganic composite separators have problems such as high surface resistance, poor hydrophilicity and low porosity in alkaline electrolytic water, which are difficult to meet the requirements of chemical corrosion resistance and mechanical strength.
The inorganic material was modified by amino acid solution, combined with polysulfone and pore-generating agent, and modified nanocomposite membranes with strong alkali corrosion resistance and good hydrophilicity were prepared through defoaming and phase conversion processes.
The prepared separator has better hydrophilicity and lower surface resistance, which significantly improves its performance in alkaline electrolytic water and provides a safer and more efficient separator solution.
Smart Images

Figure HDA0005091143720000011 
Figure HDA0005091143720000012 
Figure HDA0005091143720000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing a modified nano composite diaphragm for alkaline water electrolysis. Background Art
[0002] In the 1920s, alkaline water electrolysis for hydrogen production was industrialized and has now become very mature. Current alkaline electrolyzers usually use cheap nickel mesh as a catalyst and 20%-30% KOH solution as an electrolyte to decompose water into hydrogen and oxygen at 80°C. In order to avoid the cross-explosion of the generated hydrogen and oxygen, a porous diaphragm is used to separate the gas products. Therefore, the porous diaphragm plays a very important role in alkaline water electrolysis. Its property of separating hydrogen and oxygen can ensure the safe operation of the electrolyzer.
[0003] The porous diaphragm needs to have the following properties: 1. Excellent ion conductivity, which is conducive to the free movement of hydroxide ions between the anode and cathode; 2. Low pore size, which is conducive to preventing hydrogen permeation and avoiding short circuit; 3. Chemical corrosion resistance. The diaphragm is in a hot alkaline environment for a long time and needs extremely strong corrosion resistance; 4. It has a certain mechanical strength. The diaphragm should have a certain mechanical strength to cope with the stress and pressure generated during the production process.
[0004] At present, the synthesis method of inorganic composite membranes mainly relies on the non-solvent induced phase transition method, and the synthetic materials are mainly composed of hydrophilic oxides and support layer materials. However, the current porous inorganic membranes still have problems such as high surface resistance, poor hydrophilicity and low porosity. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a method for preparing a modified nano-composite membrane for alkaline water electrolysis. The composite membrane prepared by this method has strong alkali corrosion resistance, good hydrophilicity, high air tightness, and the preparation method is simple, easy, green and safe. Compared with commercial composite membranes, it has better hydrophilicity and lower surface resistance, which provides a new idea for the simple synthesis of other composite membranes.
[0006] The present invention provides a method for preparing a modified nanocomposite diaphragm for alkaline water electrolysis, comprising the following steps:
[0007] The inorganic material is treated with an amino acid solution to obtain an amino acid-modified hydrophilic inorganic material;
[0008] The amino acid-modified hydrophilic inorganic material, polysulfone, porogen and solvent are mixed and stirred until completely dissolved to obtain a film casting solution;
[0009] Degassing the casting solution to obtain a degassing casting solution;
[0010] Applying the degassing casting liquid on the surface of the support layer to obtain a liquid film;
[0011] Phase-transforming the liquid membrane from a poor solvent to obtain a diaphragm;
[0012] The membrane is soaked until the thickness remains unchanged to obtain a modified nanocomposite membrane.
[0013] Preferably, the amino acids in the amino acid solution are selected from one or more of tryptophan, glycine, arginine, aspartic acid and phenylalanine.
[0014] Preferably, the mass concentration of the amino acid solution is 2 to 5 mg / mL;
[0015] The mass ratio of amino acid to inorganic material is (0.015-0.06):1.
[0016] Preferably, the polysulfone is selected from polysulfones with a molecular weight of 22,000 to 80,000.
[0017] Preferably, the porogen is selected from one or more of polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60 and polyvinyl pyrrolidone K90.
[0018] Preferably, the mass ratio of polysulfone, amino acid-modified hydrophilic inorganic material and porogen is (15:70:15) to (20:60:20).
[0019] Preferably, the stirring time until complete dissolution is 5 to 24 hours;
[0020] The degassing time of the casting solution is 10 to 60 minutes.
[0021] Preferably, the material of the support layer is selected from polyetheretherketone, polyphenylene sulfide or polytetrafluoroethylene.
[0022] Preferably, the soaking temperature is 15-30°C.
[0023] The present invention provides a method for preparing a modified nano-composite diaphragm for alkaline water electrolysis, comprising the following steps: treating an inorganic material with an amino acid solution to obtain an amino acid-modified hydrophilic inorganic material; mixing the amino acid-modified hydrophilic inorganic material, polysulfone, a porogen and a solvent, stirring until completely dissolved, to obtain a casting liquid; degassing the casting liquid to obtain a degassing casting liquid; coating the degassing casting liquid on the surface of a support layer to obtain a liquid film; performing a phase transformation on the liquid film from a poor solvent to obtain a diaphragm; soaking the diaphragm until the thickness remains unchanged to obtain a modified nano-composite diaphragm. The composite diaphragm prepared by the method has strong alkali corrosion resistance, good hydrophilicity, high air tightness, and a simple, easy, green and safe preparation method. Compared with commercially available diaphragms, it has better hydrophilicity and lower surface resistance, and provides a new idea for the simple synthesis of other composite diaphragms. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a TEM image of the inorganic hydrophilic nanoparticles prepared in Example 1 of the present invention;
[0025] Figure 2 This is an XPS image of the inorganic hydrophilic nanoparticles prepared in Example 1 of the present invention;
[0026] Figure 3 This is a performance picture of the hydrophilic inorganic composite membrane prepared in Example 1 of the present invention;
[0027] Figure 4 This is a contact angle picture of the hydrophilic inorganic composite membrane prepared in Example 1 of the present invention;
[0028] Figure 5 This is a SEM image of the hydrophilic inorganic composite membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a modified nanocomposite diaphragm for alkaline water electrolysis, comprising the following steps:
[0030] The zirconium source is treated with an amino acid solution to obtain an amino acid-modified hydrophilic zirconium-containing material;
[0031] The amino acid-modified hydrophilic zirconium-containing material, polysulfone, porogen and solvent are mixed and stirred until completely dissolved to obtain a casting solution;
[0032] Degassing the casting solution to obtain a degassing casting solution;
[0033] Applying the degassing casting liquid on the surface of the support layer to obtain a liquid film;
[0034] Phase-transforming the liquid membrane from a poor solvent to obtain a diaphragm;
[0035] The membrane is soaked until the thickness remains unchanged to obtain a modified nanocomposite membrane.
[0036] The modified nano composite diaphragm prepared by the method provided by the invention has good hydrophilicity, low surface resistance and high porosity.
[0037] The present invention uses an amino acid solution to treat zirconium to obtain an amino acid-modified hydrophilic zirconium-containing material. In the present invention, the amino acid is used as a hydrophilic small molecule to modify an inorganic material zirconium source to improve its hydrophilicity; the amino acid in the amino acid solution is selected from one or more of tryptophan, glycine, arginine, aspartic acid and phenylalanine, preferably arginine and / or glycine.
[0038] The present invention dissolves amino acids in water to obtain an amino acid solution; the mass concentration of the amino acid solution is 1.5 to 6.0 mg / mL, preferably 2 to 5 mg / mL, and more preferably 3.0 to 4.5 mg / mL.
[0039] The zirconium source in the present invention is selected from one or more of zirconium chloride, zirconium oxide, zirconium nitrate, zirconium sulfate and zirconyl nitrate; more preferably zirconium oxide and / or zirconyl nitrate.
[0040] In the present invention, the mass ratio of the amino acid to the zirconium source is (0.15-0.6):90, preferably (0.4-0.6):90.
[0041] The invention allows the zirconium source and the hydrophilic small molecules to fully react by stirring; the stirring time is 22 to 26 hours. The invention centrifuges and dries the stirred mixed solution to obtain the amino acid-modified hydrophilic zirconium-containing material.
[0042] After obtaining the amino acid-modified hydrophilic zirconium-containing material, the present invention mixes the amino acid-modified hydrophilic zirconium-containing material, polysulfone, porogen and solvent, and stirs until completely dissolved to obtain a casting solution. The polysulfone in the present invention is selected from polysulfones with a molecular weight of 22,000 to 80,000. The porogen in the present invention is selected from one or more of polyvinylpyrrolidone K30, polyvinylpyrrolidone K60 and polyvinylpyrrolidone K90. The time for stirring until complete dissolution in the present invention is 5 to 24 hours.
[0043] After obtaining the casting solution, the casting solution is degassed to obtain the degassed casting solution. In the present invention, the casting solution is preferably degassed by ultrasonic degassing for 10 to 60 minutes.
[0044] After obtaining the degassing casting liquid, the present invention applies the degassing casting liquid on the surface of the support layer to obtain a liquid film. The material of the support layer in the present invention is selected from polyetheretherketone, polyphenylene sulfide or polytetrafluoroethylene. The present invention preferably uses an automatic coating machine for automatic coating to obtain a liquid film.
[0045] After obtaining the liquid membrane, the present invention performs phase transformation on the liquid membrane from a poor solvent to obtain a diaphragm. The poor solvent is selected from water. The present invention obtains the diaphragm by non-solvent induced phase separation.
[0046] The present invention uses the diaphragm prepared by the method in alkaline electrolysis of water, and exhibits the characteristics of low surface resistance, good hydrophilicity and strong air tightness.
[0047] In order to further illustrate the present invention, a method for preparing a modified nanocomposite diaphragm for alkaline water electrolysis provided by the present invention is described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0048] Example 1
[0049] Dissolve 0.45g of arginine in 100ml of deionized water, add 9.55g of ZrO2 to the solution, and stir at 30°C for 24h. Wash with deionized water, centrifuge, and dry to obtain a hydrophilic inorganic oxide. Take 7g of inorganic hydrophilic oxide, 1.5g of polyvinyl pyrrolidone and 1.5g of polysulfone and add them to 10ml of N-methylpyrrolidone solution, and stir at 30°C for 24h to obtain a casting liquid. After fixing a 270mm thick PSU support mesh on an automatic scraper, use a Meyer rod to scrape at a speed of 1cm / s to obtain a liquid film. Then put the obtained liquid film into deionized water to form a film, and replace the deionized water after five minutes to obtain a modified nanocomposite diaphragm for alkaline water electrolysis.
[0050] Figure 1 This is a TEM image of the inorganic hydrophilic nanoparticles prepared in Example 1 of the present invention.
[0051] Figure 2 This is an XPS picture of the inorganic hydrophilic nanoparticles prepared in Example 1 of the present invention. The appearance of the N element signal indicates that arginine is modified onto zirconium dioxide.
[0052] Figure 3 This is a performance picture of the amino acid-modified inorganic composite membrane prepared in Example 1 of the present invention. The results show that the voltage of the hydrophilic inorganic composite membrane is significantly lower than that of the commercial Zirfon-500 membrane on the market at the same current density.
[0053] Figure 4 This is a contact angle picture of the amino acid-modified inorganic composite membrane prepared in Example 1 of the present invention. The contact angle of the hydrophilic inorganic composite membrane prepared in Example 1 is 50°, and the contact angle of Zirfon-500 is 83°, indicating that the hydrophilicity of the membrane is better than the commercial Zirfon-500 membrane on the market.
[0054] Figure 5This is a SEM image of the amino acid-modified inorganic composite membrane prepared in Example 1 of the present invention.
[0055] The present invention adopts the current-voltage calculation test surface resistance in the alkaline water electrolysis process; and adopts the weighing method to test the porosity.
[0056] Table 1 Contact angle, surface resistance and porosity test results of the composite membrane prepared in Example
[0057] Contact angle / ° Sheet resistance Ωcm Porosity / % Example 1 50.4 0.2357 67.93 Example 2 56.8 0.3356 63.27 Example 3 63.3 0.2962 58.56
[0058] Example 2
[0059] Dissolve 0.19g of glycine in 100ml of deionized water, add 9.55g of ZrO2 to the solution, and stir at 30°C for 24h. Wash with deionized water, centrifuge, and dry to obtain a hydrophilic inorganic oxide. Take 7g of inorganic hydrophilic oxide, 1.5g of polyvinyl pyrrolidone and 1.5g of polysulfone and add them to 10ml of N-methylpyrrolidone solution, and stir at 30°C for 24h to obtain a casting liquid. After fixing a 270mm thick PSU support mesh on an automatic scraper, use a Meyer rod to scrape at a speed of 1cm / s to obtain a liquid film. Then put the obtained liquid film into deionized water to form a film, and replace the deionized water after five minutes to obtain a modified nanocomposite diaphragm for alkaline water electrolysis.
[0060] Example 3
[0061] Dissolve 0.377g of arginine in 100ml of deionized water, add 9.55g of ZrO2 to the solution, and stir at 30°C for 24h. Wash with deionized water, centrifuge, and dry to obtain a hydrophilic inorganic oxide. Take 7g of inorganic hydrophilic oxide, 1.5g of polyvinyl pyrrolidone and 1.5g of polysulfone and add them to 10ml of N-methylpyrrolidone solution, and stir at 30°C for 24h to obtain a casting liquid. After fixing a 270mm thick PSU support mesh on an automatic scraper, use a Meyer rod to scrape at a speed of 1cm / s to obtain a liquid film. Then put the obtained liquid film into deionized water to form a film, and replace the deionized water after five minutes to obtain a modified nanocomposite diaphragm for alkaline water electrolysis.
[0062] As can be seen from the above embodiments, the preparation of the inorganic composite membrane of the present invention adopts a low concentration of hydrophilic amino acid to modify the zirconium source (such as zirconium dioxide), and is simply synthesized by a solvent-induced phase separation method. The synthesis method is as follows: the hydrophilic amino acid and the zirconium source are mixed and dissolved in an aqueous solution, stirred evenly and centrifuged to obtain a modified zirconium-containing material; the modified zirconium-containing material, the polymerized monomer (such as polysulfone), and the porogen are added to a solvent (such as N-methylpyrrolidone solution) in a certain proportion and stirred evenly, and then the uniform casting liquid is scraped with a Meyer rod to obtain an inorganic membrane. The preparation process is simple, green, safe, and has a high yield, which is of great significance to the research and development of the synthesis method of the inorganic composite membrane for alkaline water electrolysis. The experimental results show that the contact angle of the composite membrane prepared by the present invention is 50.4°~63.3°, the surface resistance is 0.2357~0.3356Ωcm; and the porosity is 58.56~67.93%.
[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified nanocomposite diaphragm for alkaline water electrolysis, comprising the following steps: The zirconium source is treated with an amino acid solution to obtain an amino acid-modified hydrophilic zirconium-containing material; The amino acid-modified hydrophilic zirconium-containing material, polysulfone, porogen and solvent are mixed and stirred until completely dissolved to obtain a casting solution; Degassing the casting solution to obtain a degassing casting solution; Applying the degassing casting liquid on the surface of the support layer to obtain a liquid film; Phase-transforming the liquid membrane from a poor solvent to obtain a diaphragm; The membrane is soaked until the thickness remains unchanged to obtain a modified nanocomposite membrane.
2. The preparation method according to claim 1, characterized in that: The amino acids in the amino acid solution are selected from one or more of tryptophan, glycine, arginine, aspartic acid and phenylalanine.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the amino acid solution is 1.5 to 6.0 mg / mL; The mass ratio of amino acid to zirconium source is (0.015-0.06):
1.
4. The preparation method according to claim 1, characterized in that: The polysulfone is selected from polysulfones with a molecular weight of 22,000 to 80,000.
5. The preparation method according to claim 1, characterized in that: The porogen is selected from one or more of polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60 and polyvinyl pyrrolidone K90.
6. The preparation method according to claim 1, characterized in that: The mass ratio of polysulfone, amino acid-modified hydrophilic zirconium-containing material and porogen is (15:70:15) to (20:60:20).
7. The preparation method according to claim 1, characterized in that: The time for stirring until complete dissolution is 5 to 24 hours; The degassing time of the casting solution is 10 to 60 minutes.
8. The preparation method according to claim 1, characterized in that: The material of the support layer is selected from polyetheretherketone, polyphenylene sulfide or polytetrafluoroethylene.
9. The preparation method according to claim 1, characterized in that: The soaking temperature is 15-30°C.
Citation Information
Patent Citations
Ultralow pressure polysulfone hollow spongy membrane and preparation method thereof
CN104984669A
Surface-treated physical sun-screening agent and preparation method thereof
CN114869787A
High-conductivity alkali-resistant water electrolytic cell composite diaphragm and preparation method thereof
CN115449844A
Super-hydrophilic alkaline water electrolyser composite diaphragm and preparation method thereof
CN117248240A
Electrolytic capacitor
JP2003022938A